Efficiency Analysis of Public Service Obligation (PSO) Sea Transportation Routes in Indonesia: A Case Study of PT Pelni (Persero) - Nuraini Dessy Winiastuty; Yahya Kuncoro; Olfebri Olfebri (Dinasti International Journal of Economics, Finance & Accounting, 2026)
Maritime transportation under the Public Service Obligation (PSO) scheme plays a strategic role in ensuring interregional connectivity, particularly in Indonesia's disadvantaged, frontier, outermost, and border (3TP) areas. However, variations in the operational efficiency of PT PELNI (Persero)'s passenger ship routes may reduce the effectiveness of government subsidy utilization. This study aims to measure the operational efficiency of PSO passenger shipping routes, identify efficient and inefficient routes, and formulate operational improvement recommendations. A quantitative approach was employed using the Input-Oriented CCR Data Envelopment Analysis (DEA) model on 26 Decision Making Units (DMUs) representing PT PELNI (Persero)'s PSO passenger vessels. The input variables consist of fuel consumption, operating costs, and the number of crew members, while the output variables include the number of passengers, cargo volume, and sailing frequency. The results indicate that six vessels achieved full efficiency with a DEA score of 1.00, while the remaining twenty vessels were found to be relatively inefficient. The DEA analysis reveals that inefficiency primarily results from suboptimal utilization of operational inputs relative to the outputs produced. Based on the DEA projections, the study identified potential efficiency improvements, including a reduction of 37,599,416 liters (19%) in fuel consumption, operating cost savings of IDR 744.57 billion (18%), and optimization of 458 crew members (20%), without reducing the number of passengers, cargo volume, or sailing frequency. These findings demonstrate that DEA is an effective evaluation tool for identifying sources of operational inefficiency and achieving improvement targets to support route optimization, enhance operational performance, and provide evidence-based recommendations for a more effective, efficient, and performance-oriented PSO policy.